DAMPAK UANG SERVIS TERHADAP SEMANGAT KERJA KARYAWAN PADA PERUSAHAAN DAERAH ( PD ) HOTEL SWARNA DWIPA PALEMBANG - Romidon Hidayat (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research is to know the influence of money service to employee morale at local company (pd) Hotel Swarna Dwipa Palembang. Methods in this study quantitative methods, population in this study amounted to 122 people, sampling of 25% of 122 people as many as 31 people. Technique of collecting data using koesioner, observation and documentation. Data analysis technique use statistical test. In the analysis of statistical test data conducted in the correlation coefficient symbolized (r) obtained 0,574 then classified level of relationship is strong enough. The calculation results obtained rhitung 0.574> rtabel0,355, the value of the coefficient of determination index (r2) of 0.329 or 33% indicates the amount of influence money service to employee morale at local companies (pd) swarna dwipa hotel Palembang while the remaining 67% other. Thus it can be concluded there is a significant (positive) influence of service money on employee morale at the local company (pd) hotel swarna dwipa Palembang.Keywords : Service Money, Morale and Regional Company